Analysis of Mangrove Damage to Coastal Settlements in Muara Angke, North Jakarta - Haryeni; Eni Kamal (Postgraduate, University of Mataram, 2025)
The coastal area of Muara Angke in North Jakarta is facing increasingly serious environmental pressures due to the destruction of its mangrove ecosystem. Mangrove forests, which previously served as natural protection against ocean waves, abrasion, and tidal flooding, are now experiencing significant degradation. This phenomenon occurs in tandem with human activities such as reclamation, land conversion, and pollution. This research aims to examine in-depth the impact of mangrove destruction on coastal settlements and assess the extent to which implemented adaptation strategies can mitigate ecological and social risks. A qualitative approach with a case study design was used in this research. Data were obtained through direct field observations, interviews with the community and stakeholders, and a review of supporting documents. The analysis was conducted using a combination of descriptive techniques and evaluative instruments such as SWOT, IFAS, and EFAS to identify the strengths, weaknesses, opportunities, and threats facing the coastal area due to mangrove ecosystem degradation. The results show that mangrove destruction has a significant impact on the environmental quality of coastal communities, primarily through increased tidal flooding, abrasion, and decreased marine catches. Mitigation strategies implemented, such as the construction of stilt houses and the development of silvofishery areas, have not been fully successful due to a lack of community involvement and weak oversight. Therefore, a more participatory, integrated, and sustainability-oriented approach is needed to improve environmental conditions while enhancing the socio-economic resilience of Muara Angke residents.